Delimitation of squamous cell cervical carcinoma using infrared microspectroscopic imaging. - Steller, W.; Einenkel, J.; Horn, L. C.; Braumann, U. D.; Binder, H.; Salzer, R.; Krafft, C. (Anal Bioanal Chem, 2006)
Infrared (IR) spectroscopic imaging coupled with microscopy has been used to investigate thin sections of cervix uteri encompassing normal tissue, precancerous structures, and squamous cell carcinoma. Methods for unsupervised distinction of tissue types based on IR spectroscopy were developed. One-hundred and twenty-two images of cervical tissue were recorded by an FTIR spectrometer with a 64x64 focal plane array detector. The 499,712 IR spectra obtained were grouped by an approach which used fuzzy C-means clustering followed by hierarchical cluster analysis. The resulting false color maps were correlated with the morphological characteristics of an adjacent section of hematoxylin and eosin-stained tissue. In the first step, cervical stroma, epithelium, inflammation, blood vessels, and mucus could be distinguished in IR images by analysis of the spectral fingerprint region (950-1480 cm(-1)). In the second step, analysis in the spectral window 1420-1480 cm(-1) enables, for the first time, IR spectroscopic distinction between the basal layer, dysplastic lesions and squamous cell carcinoma within a particular sample. The joint application of IR microspectroscopic imaging and multivariate spectral processing combines diffraction-limited lateral optical resolution on the single cell level with highly specific and sensitive spectral classification on the molecular level. Compared with previous reports our approach constitutes a significant progress in the development of optical molecular spectroscopic techniques toward an additional diagnostic tool for the early histopathological characterization of cervical cancer.
Keywords: Carcinoma, Squamous Cell/*pathology; Cluster Analysis; Eosine Yellowish-(YS); Epithelium/pathology; Female; Hematoxylin; Humans; Spectrophotometry, Infrared/*methods; Stromal Cells/pathology; Uterine Cervical Neoplasms/*pathology